Модель процесу видобутку нафти і газу як сфери походження специфічних функцій і задач управління - Василик, І. І.; Vasylyk, І. (КНТУ, 2013)
Визначено глобальні, часткові і кінцеві цілі процесу видобутку нафти і газу та охарактеризовано основні поняття, які слід використовувати при побудові даної моделі. Побудовано модель процесу видобутку нафти і газу як сфери походження специфічних функцій і задач. The purpose of the article is a construction of model of the oil and gas production process as spheres of origin of specific functions and tasks. As a purpose of the oil and gas production process is a booty of oil, gas and gas runback and receipt of commodity products, the global, partial and eventual aims of this process were considered in this context. A prototype for the construction of model was become by the multidimensional model of process of labour, where components (factors) of process of labour and functional control system are, their co-operation in an aggregate form the system «process of labour». The theoretical model of the oil and gas production process is offered, he is considered as unity of process of labour and process of formation of cost, as unity of the guided and managing subsystems,
Model of the oil and gas production process as spheres of origin of specific functions and management tasks
Keywords: процес видобутку нафти і газу; модель; праця; предмети праці; засоби праці; управління процесом видобутку нафти і газу; the oil and gas production process; model; labour; articles of labour; facilities of labour; management of the oil and gas production process